COVID19 outbreak impact on international stock markets colatility contagion; Impacto del estallido de COVID19 en la volatilidad de los mercados de capital internacionales - Magnolia Miriam Sosa Castro; Edgar Ortiz; Alejandra Cabello-Rosales (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
We analyze volatility contagion between the U.S. and Chinese stock markets and international capital markets. The volatility is modeled using: GARCH, TARCH, EGARCH, APARCH, IGARCH, FIGARCH, ACGARCH and GAS models under Gaussian, GED and t-Student distributions. 21,000 intraday observations of thirteen markets from January/1st to June/25th 2020 are employed. Once volatility is modeled, the incidence of Chinese and American markets on the rest of the bourses is tested employing Vector Autoregressive Markov Switching Models. Evidence confirms incidence of the Chinese and American capital markets volatility in other markets volatility; common breakpoints and Intermarket incidence in high volatility periods stand out.
Keywords: G01; G15; F36; C57; C58; 330; volatility contagion; Markov Switching Model; Garch Approach; Stock Markets; Covid 19